The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1080/01402382.2015.1062252
|View full text |Cite
|
Sign up to set email alerts
|

Local, National and Global Islam: Religious Guidance and European Muslim Public Opinion on Political Radicalism and Social Conservatism

Abstract: Abstract:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
1
7
0
1
Order By: Relevance
“…As per the above, the average rate of justification of terrorism according to the 2008 European Values Survey was 5.6%. This number is similar to what has been found in Western European countries in the 2006 PEW Global Values Survey, according to which the combined response for suicide bombings being rarely, sometimes and often justified, was 4.3% (e.g., Berger, 2016; Zhirkov et al., 2014). The responses for U.S. samples have been somewhat similar.…”
supporting
confidence: 85%
“…As per the above, the average rate of justification of terrorism according to the 2008 European Values Survey was 5.6%. This number is similar to what has been found in Western European countries in the 2006 PEW Global Values Survey, according to which the combined response for suicide bombings being rarely, sometimes and often justified, was 4.3% (e.g., Berger, 2016; Zhirkov et al., 2014). The responses for U.S. samples have been somewhat similar.…”
supporting
confidence: 85%
“…Victimization and discrimination can lead to feelings such as anger and a desire for revenge, and accordingly increase the likelihood of radicalization (Bjørgo, 2005;Dandurand, 2014). Similar to relative deprivation perspectives, victimization or perceptions of discrimination, racism, and injustices at both the individual and group level can be risk factors for radicalization (Berger, 2016;Brettfeld & Wetzels, 2007;Bhui et al, 2014b;McCauley, 2012;Pauwels & de Waele, 2014;Simons et al, 2003;de Waele & Pauwels, 2014). When individuals view a lack of governmental action being taken to combat discrimination, it can erode existing levels of integration and institutional trust.…”
Section: Integration Trust and Discriminationmentioning
confidence: 99%
“…Radicalisation per se has even evolved to be individual radicalisation (lone wolf radicalisation ), in which the prevention requires monitoring of the community and the Internet to detect and manage threats (Dechesne & Meines, 2012). Berger (2016) found that radicalisation has some im-278 CEJISS 4/2019 plications for Western European governments in shaping security policies and creating social cohesion. However, Vidino & Brandon (2012) suggest that the characteristics, philosophies, goals and challenges of counter-radicalisation strategies in various European countries need to consider the unique political, cultural and legal elements in each society.…”
Section: Rmt Nurhasan Affandi Windy Dermawanmentioning
confidence: 99%